An Institutional Regulatory Analysis for Genetically Modified Products with special reference to Bt Mustard: An Institutional Regulatory Analysis for Genetically Modified Products with special reference to Bt Mustard - ABHISHEK AGNIHOTRI (Journal of Oilseeds Research, 2023)
Rules for the Manufacture, Use/Import/Export, and Storage of Hazardous Micro Organisms/Genetically Engineered Organisms or Cells, 1989 has laid down several guidelines to ensure environmental safety in the use of genetically modified organisms (GMOs) and to provide regulatory approvals for dealing with genetically engineered (GE) entities.A few committees have been constituted under the 1989 rules and the Recombinant DNA (rDNA) safety guidelines, 1990 at the institutional level, including Genetic Engineering Approval Committee (GEAC). The Paper intends to analyze policy initiatives in the direction of biotechnology regulation in India, especially after the petition was filed opposing the government's approval of field trials for GM crops. The petitioner has sought Supreme Court's intervention in the matter with a clear direction to the government for not pushing and going ahead with the approval of field trials of GM crops.